2018
DOI: 10.15252/embj.201899021
|View full text |Cite
|
Sign up to set email alerts
|

Histone H2A‐H2B binding by Pol α in the eukaryotic replisome contributes to the maintenance of repressive chromatin

Abstract: The eukaryotic replisome disassembles parental chromatin at DNA replication forks, but then plays a poorly understood role in the re‐deposition of the displaced histone complexes onto nascent DNA. Here, we show that yeast DNA polymerase α contains a histone‐binding motif that is conserved in human Pol α and is specific for histones H2A and H2B. Mutation of this motif in budding yeast cells does not affect DNA synthesis, but instead abrogates gene silencing at telomeres and mating‐type loci. Similar phenotypes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
55
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 67 publications
1
55
2
Order By: Relevance
“…It is worth mentioning that the mutation that abolished the histone-binding activity of Mcm2 disrupted the association between Pol α and Mcm2 without affecting the interaction of Pol α with Ctf4. Disrupting the H2A-H2B-binding site of Pol α led to similar results [148]. Early studies also showed that Pol α can bind FACT [151][152][153].…”
Section: Dna Polymerases: Key Players In Histone Segregation On Daughmentioning
confidence: 84%
See 3 more Smart Citations
“…It is worth mentioning that the mutation that abolished the histone-binding activity of Mcm2 disrupted the association between Pol α and Mcm2 without affecting the interaction of Pol α with Ctf4. Disrupting the H2A-H2B-binding site of Pol α led to similar results [148]. Early studies also showed that Pol α can bind FACT [151][152][153].…”
Section: Dna Polymerases: Key Players In Histone Segregation On Daughmentioning
confidence: 84%
“…Moreover, disrupting the histone-binding ability of either Pol ε or Pol α impaired parental histone segregation on daughter strands, indicating a direct role of polymerase in RC nucleosome assembly. Supporting this idea, mutations disrupting the Pol α-H2A-H2B interaction and the Pol α-Ctf4 interaction led to silencing loss in telomeric regions and at mating type loci [148]. Pol α was also important for heterochromatin silencing maintenance in fission yeast and the restoration of repressive histone marks in plants [159,160].…”
Section: Dna Polymerases: Key Players In Histone Segregation On Daughmentioning
confidence: 92%
See 2 more Smart Citations
“…These include Ctf4 (And-1), Mrc1 (Claspin) and Csm3/Tof1 (Tipin/Timeless) that were identified as components of replisome progression complexes -stable CMG-containing complexes isolated from S-phase yeast cells (Gambus et al, 2006). Ctf4 is a trimeric hub that recruits proteins involved in sister chromatid cohesion, ribosomal DNA maintenance, parental histone transfer and gene silencing (Evrin et al, 2018;Gan et al, 2018;Samora et al, 2016;Simon et al, 2014;Villa et al, 2016). Csm3/Tof1 and Mrc1 are key replisome modulators, collectively termed the fork protection complex, that intimately associate with one another, both physically and functionally Katou et al, 2003).…”
mentioning
confidence: 99%